A PORTRAIT OF TEACHING ENGLISH VOCABULARY THROUGH SONGS TO YOUNG LEARNERS : A Case Study in TK Gagas Ceria Bandung - Rifayanti, Dewi (2013)
The research entitled A PORTRAIT OF TEACHING ENGLISH VOCABULARY THROUGH SONGS TO YOUNG LEARNERS (A Case Study in TK GagasCeria Bandung) was aimed to capture English vocabulary teaching through songs in TK GagasCeria. Specifically, this research is aimed at portraying kinds of song-based activities implemented in young learners' classroom and teacher's considerations in implementing the song-based activities. This research employed a case study of teaching English vocabulary through songs to young learners. A class was selected as the sample of the research. The data were taken from the classroom observations including field notes, song-based checklists; as well interviews and written documents.The song-based activities to teach English vocabulary to young learners capture during observation included choral singing, games, role play, story time, and song-based assessment. The activities were also planned in the daily lesson plan. The songs' lyric used in the classroom were originally made for the context of vocabulary target on different themes. The children's learning styles considered by the teacher in implementing the song-based activities were auditory, visual, and kinesthetic. Auditory learning style facilitated through songs, visual learning style through pictures and real objects, and kinesthetic learning style through movements. It is recommended to teach vocabulary through songs for young learners since it has benefits. Songs create a joyful atmosphere for young foreign language learners, context to teach English vocabulary, and give children more opportunity to listen the vocabulary targets as many as possible before they can produce and use the vocabulary. Key words: teaching vocabulary, song-based learning, vocabulary learning, and young learners. Penelitian dengan judul A PORTRAIT OF TEACHING ENGLISH VOCABULARY THROUGH SONGS TO YOUNG LEARNERS (Sebuah Studi Kasus di TK GagasCeria Bandung) bertujuan untuk memotret pengajaran kosakata berbahasa Inggris melalui lagu di taman kanak-kanak. Secara khusus, penelitian ini memotret jenis-jenis aktifitas yang dilakukan di dalam kelas dan pertimbangan guru saat menerapkan aktifitas-aktifitas tersebut.Penelitian ini menggunakan studi kasus untuk mengetahui pengajaran kosakata bahasa Inggris melalui lagu. Data diambil melalui observasi sebuah kelas di taman kanak-kanak, termasuk catatan, song-based checklists; juga wawancara dan dokumen tertulis.Beberapa aktifitas yang ditemukan melalui penelitian ini adalah choral singing, games, role play, story time, dan asesmen melalui lagu (song-based assessment).Aktifitas yang dilakukan juga direncanakan melalui lesson plan. Lirik lagu yang digunakan di kelas juga dibuat secara original sesuai dengan tema untuk pengajaran kosakata di kelas.Pembelajaran melalui lagu juga memfasilitasi gaya belajar anak, seperti auditori, visual, dan kinestetik. Gaya belajar auditori difasilitasi melalui lagu, visual melalui gambar dan benda nyata, dan kinestetik melalui gerakan. Mengajar kosakata berbahasa Inggris melalui lagu sangat direkomendasikan. Beberapa manfaat mengajarkan kosakata melalui lagu diantaranya, lagu membuat anak lebih relax, lagu membuat pengajaran kosakata lebih kontekstual, dan memberi anak kesempatan untuk mendengarkan target kosakata sebelum dapat menggunakannya. Kata kunci: pengajaran kosakata, pembelajaran berdasarkan lagu, pembelajaran kosakata, dan pelajar usia dini.